Farm animals - Legendre, Philippe (Laguna Hills, CA : Walter Foster Pub., 1992)
With basic shapes you can create a cow, pig, horse, or any farm animal.
"A child's first drawing book"--Cover.
Keywords: Domestic animals in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Animals in art. -- Juvenile literature -- Technique